Evaluation of Mechanical Properties of Particulate Composites - Jweeg, Muhsin J.; Abd, Abdul Rahman Najim; Abdulrazzag, Nowfal A. (Al-Khwarizmi Engineering Journal, 2010)
A series of experiments have been taken out to test the validity of the effect of Aluminum hydrate on its interaction with Aluminum during sintering of aluminum metal matrix. The approach has been shown to be valid and several compositions have been fabricated. The alumina hydrate particle size and the amount of alumina hydrate in the composites are also shown to have an influence on the extent of densification. The densities for all sintered specimens were measured. It was found that density increases as compaction pressure increases, the density decreases as particles size increases. At 400 MPa there is an optimum particles size which is (90-125) µm to reach maximum density and the density decreases as volume fraction increases from 2% to 20%. The microstructure enhances as compaction pressure increases, agglomeration of alumina hydrate particles increases with increasing of volume fraction and cavities increases especially at low compaction pressure more than at high compaction pressure. The mechanical properties (compression test and Vickers hardness) of sintered specimens compacted at 100 MPa accomplished for three volume fractions 2%, 10% and 20% and three particles size (45-90) µm, (90-125) µm and (125-150) µm. Young’s modulus in compression decreases as volume fraction increases. Also it decreases as particles size increases and Vickers hardness decreases as volume fraction increases. Also decreases as particles size increases.